The Criminalization of Civil Disputes: A Legal Analysis of the Application of Criminal Charges in Cases Involving State Finances - Nurmalah Nurmalah; Hamzeh Abu Issa; Hendro Widodo; HD Djunaedi; Andhika Yuli Rimbawan (Jurnal Hukum, 2025)
The phenomenon of criminalization of civil disputes involving state finances has created controversy in Indonesian legal practice. The unclear boundary between administrative-civil state losses and corruption has led to law enforcement practices that often exceed the principle of ultimum remedium. This paper aims to analyze the legal application of criminal charges in civil cases impacting state finances by examining the normative framework, court decisions, and the practice of calculating state losses by state auditors. This research uses a normative-doctrinal approach through analysis of laws, decisions of the Constitutional Court and the Supreme Court, and concrete case studies. The results of the study indicate that inconsistent definitions of "state losses" and the absence of standard calculation methods increase the risk of criminalization of acts that should be resolved administratively or civilly. This article recommends the need for standardization of audit methodology, strengthening the mechanism for claiming compensation for state losses in the administrative realm, and affirming the principle of ultimum remedium in prosecution policy.